2018
DOI: 10.1039/c8cc03883j
|View full text |Cite
|
Sign up to set email alerts
|

Chirality sensing of choline derivatives by a triple anion helicate cage through induced circular dichroism

Abstract: Chirality sensing of choline derivatives is achieved by a self-assembled, racemic triple anion helicate cage which exhibits induced circular dichroism (ICD) upon encapsulation of a chiral guest. The host-guest interactions were illustrated by NMR, crystal structure, CD and DFT calculations. The absolute configurations and ee values were determined by ICD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 59 publications
3
37
0
Order By: Relevance
“…The tripodal hexa-urea L 1 (Scheme 1)13 and related ligands14 display efficient coordination with the divalent sulfate ion. Recently, the triple anion helicate formed from a bis–bis(urea) ligand with a methylene-diphenylene spacer was found to exhibit an ‘aromatic box’ that can selectively bind choline and its derivatives 15. Therefore, we reasoned that the hexa-urea moiety with aromatic terminal groups may provide the necessary dual binding sites for the anionic choline phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…The tripodal hexa-urea L 1 (Scheme 1)13 and related ligands14 display efficient coordination with the divalent sulfate ion. Recently, the triple anion helicate formed from a bis–bis(urea) ligand with a methylene-diphenylene spacer was found to exhibit an ‘aromatic box’ that can selectively bind choline and its derivatives 15. Therefore, we reasoned that the hexa-urea moiety with aromatic terminal groups may provide the necessary dual binding sites for the anionic choline phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Host-guest chemistry is an alternative method to expand the substrate scope of CD-based chiroptical sensing.F or example,B iedermann and Nau [8] have reported that the complexes of cucurbit [8]uril with dicationic dyes can be applied in chiroptical sensing of av ariety of biological molecules and drug molecules in water. This strategy is general in terms of functional groups but limited to molecules with an aromatic group next to their chiral centers.A cyclic cucurbit[n]urils and molecular tweezers, [9] pillar[n]arenes, [10] calix[n]arene, [11] resorcinarene, [12] covalent cage molecules, [13] foldamers, [14] and helicates [15] with aromatic sidewalls have also been demonstrated as chirality sensors.But the guests are still limited to aromatic compounds,c harged organic compounds,o rr igid molecules.M olecular sensors with aw ide substrate scope still remain to be developed for optical chirality sensing.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is general in terms of functional groups but limited to molecules with an aromatic group next to their chiral centers. Acyclic cucurbit[ n ]urils and molecular tweezers, [9] pillar[ n ]arenes, [10] calix[ n ]arene, [11] resorcinarene, [12] covalent cage molecules, [13] foldamers, [14] and helicates [15] with aromatic sidewalls have also been demonstrated as chirality sensors. But the guests are still limited to aromatic compounds, charged organic compounds, or rigid molecules.…”
Section: Introductionmentioning
confidence: 99%